Boosting O2− Photogeneration via Promoting Intersystem‐Crossing and Electron‐Donating Efficiency of Aza‐BODIPY‐Based Nanoplatforms for Hypoxic‐Tumor Photodynamic Therapy. Issue 7 (19th April 2020) - Chen, Dapeng; Wang, Zhichao; Dai, Hanming; Lv, Xinyi; Ma, Qianli; Yang, Da‐Peng; Shao, Jinjun; Xu, Zhigang; Dong, Xiaochen
Abstract: Tumor hypoxia severely impedes the therapeutic efficacy of type II photodynamic therapy (PDT) depending on singlet oxygen ( 1 O2 ) generation. To combat hypoxic tumors, herein, a new approach is devised to boost superoxide radical (O2 − ) photogeneration for type I PDT. Heavy atoms are introduced onto aza‐BODIPY molecules (iodine substituted butoxy‐aza‐BODIPY, IBAB) to promote their intersystem‐crossing (ISC) ability. Meanwhile, methoxy‐poly(ethylene glycol)‐ b ‐poly(2‐(diisopropylamino) ethyl methacrylate) (mPEG‐PPDA) with enhanced electron‐donating efficiency is employed as a coating matrix to encapsulate IBAB, thereby obtaining amphiphilic aza‐BODIPY nanoplatforms (PPIAB NPs). Under irradiation, triplet‐state IBAB in PPIAB NPs is efficiently generated from singlet state favored by the elevated ISC ability. The electron‐rich environment provided by mPEG‐PPDA can donate triplet‐state IBAB with one electron to form charge‐separated‐state IBAB, which in turn transfers electron to O2 for O2 − production. Significantly, owing to recyclable O2 generated by disproportionation or Harber–Weiss/Fenton reaction, prominent O2 − is generated by PPIAB NPs even in a severe hypoxic environment (2% O2 ), enabling superior therapeutic efficacy (96.2% tumor‐inhibition rate) over NPs not following this strategy. Thus, the proof‐of‐concept design of ISC‐enhanced and electron‐rich polymer encapsulating PPIAB NPs illuminates the path to preparing O2 − photogenerator for hypoxic cancer treatment. Abstract : This study devises a new approach to boost O2 − photogeneration for type I photodynamic therapy (PDT). By improving the photosensitizers' intersystem‐crossing ability and coating polymers' electron‐donating ability, amphiphilic aza‐BODIPY nanoplatforms (PPIAB NPs) with O2 − photogeneration ability are obtained. PPIAB NPs can achieve remarkable PDT efficacy in hypoxia, illuminating the path to preparing O2 − photogenerators for cancer treatment in the future.